Outcome-specific park-catchment assessment of age-supportive neighborhood parks using field audits and street-view imagery - Li-Chih Ho; Yu-Sheng Shen; Sin-Rou Fu; Po-Ju Chang (Landscape and Ecological Engineering, 2026)

A national-scale early detection and rapid response (EDRR) to invasive cane toads (Rhinella marina) in Taiwan - Yung-Chih Lai; Chun-Fu Lin; Li-Mien Tseng; Cheng-En Li; Jia-Han Lee; Jou-Yun Chen; Ming-Chih Wang; Chun-Hung Lai; Yueh-Feng Chen; Chun-Lin Ho; Wei-Chun Cheng; Yi-Ju Yang (Biological Invasions, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Strategies for smoke control in tunnel fires: Approaches from numerical and experimental studies - Chin-Feng Chen; Hsin-Hsiu Ho; Ping-Jung Li; Yuan-Ming Chiu; Chih-Yuan Weng; Yu-Jen Chen (Process Safety and Environmental Protection, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunology, 142: 109,134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Research note: assessing human preferences for natural landscapes—an analysis of ChatGPT-4 and LLaVA models - Yu-Hsin Tung; Zhe-Rui Yang; Meng-Wei Shen; Chun-Yen Chang; Chien-Chung Chen; Li-Chih Ho (Landscape and Urban Planning, 2025)

Corrigendum to “Assessment of Bacillus subtilis fermented Caulerpa microphysa by product as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei)” [Fish & Shellfish Immunol. (2023) 142 109134] - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Mitigating non-point source pollution in tea plantations: SWAT modeling and field validation of slow-release fertilizers - Chia-Chun Ho; Pin-Chih Shih; Li-Chi Chiang; Yi-Xuan Lin; Hsiu-Feng Liu; Wen-Guei Chang; Guan-Zhou Lin (Environmental Monitoring and Assessment, 2025)

Singular value decomposition of near-field electromagnetic data for compressing and accelerating deep neural networks in the prediction of geometric parameters for through silicon via array - Song-En Chen; Eugene Su; Chih-Chung Wang; Jia-Han Li; Chao-Ching Ho (Computer Physics Communications, 2025)

Comparison of street and pedestrian views: categorizing environmental color using deep learning - Pei-Yi Weng; Li-Chih Ho; Dongying Li; Yen-Cheng Chiang (Landscape and Ecological Engineering, 2025)

Functional identification of specialized diterpene synthases from Chamaecyparis obtusa and C. obtusa var. formosana to illustrate the putative evolution of diterpene synthases in Cupressaceae - Tsai-Jung Wu; Chi-Chun Lin; Li-Ting Ma; Chih-Kai Yang; Chen-Lung Ho; Sheng-Yang Wang; Fang-Hua Chu (Plant Science, 2024)

Impact of metformin on neocortical development during pregnancy: Involvement of ERK and p35/CDK5 pathways - Muhammet Oner; Mei-Chih Chen; Pang-Ting Cheng; Yu-Hsuan Li; Yu-Chiao Cheng; Ayse Celik; Shiuan-Woei Soong; Li-Wen Hsu; Din-You Lin; G.M. Shazzad Hossain Prince; Trayee Dhar; Hsu-Chen Cheng; et al. (Chemosphere, 2024)

Spatiotemporal characterization of PM2.5, O3, and trace gases associated with East Asian continental outflows via drone sounding - Chih-Yuan Chang; Jia-Lin Wang; Yen-Chen Chen; Wei-Nai Chen; Sheng-Hsiang Wang; Ming-Tung Chuang; Neng-Huei Lin; Charles C.-K. Chou; Wei-Syun Huang; Li-Jin Ke; Xiang-Xu Pan; Yu-Jui Ho; et al. (Science of The Total Environment, 2024)

Investigating the interplay between senior-friendly park features, perceived greenness, restorativeness, and well-being in older adults - Po-Ju Chang; Li-Chih Ho; Pongsakorn Suppakittpaisarn (Urban Forestry & Urban Greening, 2024)

Photocurable 3D-printed AgNPs/Graphene/Polymer nanocomposites with high flexibility and stretchability for ECG and EMG smart clothing - Jia-Wun Li; Ho-Fu Chen; Yu-Zhe Liu; Jui-Hsin Wang; Ming-Chang Lu; Chih-Wei Chiu (Chemical Engineering Journal, 2024)

Assessment of Bacillus subtilis fermented Caulerpa microphysa byproduct as feed additive on the growth performance, immune regulation and disease resistance of white shrimp (Litopenaeus vannamei) - Meng-Chou Lee; Ching-Tien Lo; Thi Hang Ho; Li-Li Chen; Fan-Hua Nan; Hung-Chih Lai; Eakapol Wangkahart; Po-Tsang Lee (Fish & Shellfish Immunology, 2023)

Quantity and quality: Role of vegetation in park visitation and physical activity - Yen-Cheng Chiang; Pei-Yi Weng; Dongying Li; Li-Chih Ho (Landscape and Ecological Engineering, 2023)

Quantification through deep learning of sky view factor and greenery on urban streets during hot and cool seasons - Yen-Cheng Chiang; Ho-Hsun Liu; Dongying Li; Li-Chih Ho (Landscape and Urban Planning, 2023)

Preliminary Measurements of Binaural Masking-Level Difference When Using Hearing Aids for Sensorineural Hearing Loss - Cheng-Yu Ho; Pei-Chun Li; Shuenn-Tsong Young; Wen-Ying Yeh; Chih-Hung Wang; Woei-Chyn Chu (Journal of Medical and Biological Engineering, 2016)

Loss of Egr-1 sensitizes pancreatic β-cells to palmitate-induced ER stress and apoptosis - Mun-Wai Cheong; Li-Hua Kuo; Yi-Ning Cheng; Pei-Jane Tsai; Li-Chun Ho; Haw-Chih Tai; Wen-Tai Chiu; Shun-Hua Chen; Pei-Jung Lu; Yan-Shen Shan; Lee-Ming Chuang; Yau-Sheng Tsai (Journal of Molecular Medicine, 2015)

Rapid optimization of drug combinations for the optimal angiostatic treatment of cancer - Andrea Weiss; Xianting Ding; Judy R. van Beijnum; Ieong Wong; Tse J. Wong; Robert H. Berndsen; Olivier Dormond; Marchien Dallinga; Li Shen; Reinier O. Schlingemann; Roberto Pili; Chih-Ming Ho; et al. (Angiogenesis, 2015)
Drug combinations can improve angiostatic cancer treatment efficacy and enable the reduction of side effects and drug resistance. Combining drugs is non-trivial due to the high number of possibilities. We applied a feedback system control (FSC) technique with a population-based stochastic search algorithm to navigate through the large parametric space of nine angiostatic drugs at four concentrations to identify optimal low-dose drug combinations. This implied an iterative approach of in vitro testing of endothelial cell viability and algorithm-based analysis. The optimal synergistic drug combination, containing erlotinib, BEZ-235 and RAPTA-C, was reached in a small number of iterations. Final drug combinations showed enhanced endothelial cell specificity and synergistically inhibited proliferation ( p p p p

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Development and characterization of nine polymorphic microsatellite markers from the sword prawn Parapenaeopsis hardwickii using PCR-based isolation of microsatellite arrays (PIMA) - Chuan-Wen Ho; Tzong-Der Tzeng; Tzen-Yuh Chiang; Chih-Yao Li; Feng-Jiau Lin (Conservation Genetics Resources, 2014)

Yeast Oropharyngeal Colonization in Human Immunodeficiency Virus-Infected Patients in Central Taiwan - Mao-Wang Ho; Yun-Liang Yang; Chih-Chao Lin; Chih-Yu Chi; Hui-Ting Chen; Po-Chang Lin; Li-Yun Hsieh; Chia-Hui Chou; Wen-Li Chu; Chiou-Pyng Wu; Tsai-Ling Lauderdale; Hsiu-Jung Lo (Mycopathologia, 2014)

Gelsolin (GSN) induces cardiomyocyte hypertrophy and BNP expression via p38 signaling and GATA-4 transcriptional factor activation - Wei-Syun Hu; Tsung-Jung Ho; Peiying Pai; Li-Chin Chung; Chia-Hua Kuo; Sheng-Huang Chang; Fuu-Jen Tsai; Chang-Hai Tsai; Yu-Chi Jie; Ying-Ming Liou; Chih-Yang Huang (Molecular and Cellular Biochemistry, 2014)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

β-Actin is a downstream effector of the PI3K/AKT signaling pathway in myeloma cells - Yen-Peng Ho; Chi-Wei Kuo; Yuan-Tong Hsu; Yu-Shan Huang; Li-Ping Yew; Wei-Feng Huang; Kuo-Chih Lin; Jung-Hsin Hsu (Molecular and Cellular Biochemistry, 2011)

TCF7L2 genetic variants and progression to diabetes in the Chinese population: pleiotropic effects on insulin secretion and insulin resistance - Yi-Cheng Chang; Yen-Feng Chiu; Larry Low-Tone Ho; Chih-Tai Ting; Kuang-Chung Shih; J. David Curb; Yii-Der Ida Chen; Hung-Yuan Li; Lee-Ming Chuang (Journal of Molecular Medicine, 2010)

Increased Risk of Developing Hepatocellular Carcinoma Associated with Carriage of the TNF2 Allele of the −308 Tumor Necrosis Factor-α Promoter Gene - Sheng-Yow Ho; Ying-Jan Wang; Hen-Li Chen; Chih-Hung Chen; Chih-Jen Chang; Po-Jen Wang; Helen H.W. Chen; How-Ran Guo (Cancer Causes & Control, 2004)